Torsadogenic Index: A Proposal to Improve Survival Rates in Cardiac Arrests Due to Prescribed Drugs - Inchauspe, Adrián Angel A. (Frontiers in Pharmacology, 2012)
Since unexpected sudden deaths have been reported with the use of diversal non-cardiac drugs, cardio-safety experts focused their attention on security measures to improve survival rates in heart stoppages due to this prescribed drugs. Considering that prolongation of the QTc is a reliable marker of a menacing arrhythmia called torsade de pointes (TdP) - that can progress to ventricular fibrillation, application of Bazett or Rautaharhu formulas can lead to a proper predictive valuation of a "torsadogenic risk". Case-analysis raises up the proposal that QTc or QTp will allow to identify high risk groups; performs a close pharmaco- vigilance and legally register ECG follow -up, avoiding unnecessary withdrawal of useful drugs from market.